STUDI KELAYAKAN STABILITAS BENDUNG TERHADAP GESER, GULING DAN DAYA DUKUNG TANAH DI BENDUNG CIANTEN 1B - Winda Harsanti, Moch. Khamim (Prokons: Jurnal Teknik Sipil, 2018)
Weir is a river transverse building that is served to raise the river water. Cianten River is one of the rivers that need this building, because the water level planned to be used for micro power plant is not sufficient. The planned weir dimension needs to be analyzed for its stability. From the analysis results it is known that for stability against bolsters and soil bearing capacity has a safety factor above the minimum number. But for the stability of the shear and the crawl is below the minimum safety number. To solve this problem, the foundation of weir needs to be lengthened.                Keywords: safety factor, stability, weir